Microplastic detection and remediation through efficient interfacial solar evaporation for immaculate water production - Yu, Zhen (2024)
Freshwater scarcity and microplastics (MPs) pollution are two concerning and intertwined global challenges. In this work, we propose a "one stone kills two birds" strategy by employing an interfacial solar evaporation platform (ISEP) combined with a MPs adsorbent. This strategy aims to produce clean water and simultaneously enhance MPs removal. Unlike traditional predecessors, our ISEP generates condensed water free from MPs contamination. Additionally, the photothermally driven interfacial separation process significantly improves the MPs removal performance. We observed a removal ratio increase of up to 5.5 times compared to previously reported MPs adsorbents. Thus, our rationally-designed ISEP holds promising potential to not only mitigate the existing water scarcity issue but also remediate MPs pollution in natural water environments.